Taxonomia, numeros cromossomicos e quimica de especies de Crotalaria L. (Leguminosae-Papilionoideae) no Brasil - Flores, Andreia Silva (2004)
Orientadores: Ana Maria Goulart de Azevedo Tozzi, Jose Roberto Trigo